Gender differences in perception of psychosocial distress and coping mechanisms among infertile men and women in Saudi Arabia. (2nd January 2017) - Alosaimi, Fahad D.; Bukhari, Mujahid; Altuwirqi, Maram; Habous, Mohamad; Madbouly, Khaled; Abotalib, Zeinab; Binsaleh, Saleh
Abstract: The objective of the study was to evaluate the differences in psychosocial distress and coping mechanisms among infertile men and women in Saudi Arabia (SA). We performed a cross-sectional study of infertile patients (206 women and 200 men) attending infertility clinics in three referral hospitals in Riyadh, SA. A semi-structured questionnaire was developed to assess socio-demographic, clinical and psychosocial variables. Infertility-related psychosocial pressures were reported in 79 (39.7%) male and 97 (47.3%) female participants ( p  = 0.123). Males suffered more from intrusive questions and pressure to conceive, remarry or get divorced, while females were stressed more from psychological and emotional exhaustion, marital discord, attitudes of mothers-in-law or society, and persistent desire by the husband to have children. To cope with infertility, females engaged more in religious activities ( p < 0.001) and spoke more to someone regarding their problems ( p < 0.001). To solve their infertility problems, 50% tried to find solutions via the internet, and 38.5% of males and 51% of females reported using alternative medicines ( p = 0.012). The patients with infertility in SA face multiple psychosocial stressors related to their infertility, and cope differently based on the gender and culture-specific knowledge of infertility. The female participants were significantly more affected from psychosocial stressors and the persistent desire by their spouse to have children.